Toward High‐Performance Carbon Nanotube Photovoltaic Devices. Issue 17 (2nd June 2016) - Liu, Yang; Wang, Sheng; Peng, Lian‐Mao
Abstract : Photovoltaic (PV) infrared (IR)‐based devices are important for a variety of industrial and scientific applications, such as IR imaging, biological sensing, day–night surveillance and in solar cells. However, most high‐end IR PV devices made of conventional semiconductors need to be cooled to achieve high performance, while these materials usually are also not stable under strong illumination. Carbon nanotubes (CNTs) are direct‐bandgap materials with a broad spectral response and a large absorption coefficient, which is most desired for building high‐performance PV devices. Main progresses on CNT PVs in the past 15 years is reviewed, emphasizing recent breakthrough of CNT IR photodetectors based on solution‐processed high‐purity CNT films via a doping‐free fabrication technique. This technique has been combined with virtual contacts to multiply the photovoltage and thus to significantly improve detection performance and signal‐to‐noise ratio of PV detectors. It is demonstrated that this CNT PV detector has a superior broadband response from visible to near‐infrared light, high room‐temperature detectivity comparable with state‐of‐the‐art InGaAs detectors, and extremely good temperature and temporal stability. Challenges that still lay ahead and possible solutions are discussed. Abstract : The development of carbon nanotubes (CNT) photovoltaics with an emphasis on recent breakthroughs is reviewed. CNT IR (infrared) cascading photodetectors, based on high‐purity solution‐processed CNT films via the doping‐free technique, exhibit a superior broadband response from visible to near‐infrared, high room‐temperature detectivity comparable to state‐of‐the‐art InGaAs detectors, and extremely good temperature and temporal stability.